Changes in the quality of life of adults with sickle cell disease following allogeneic stem cell transplantation: A mixed‐methods, prospective cohort study - Elisabeth Dovern; Sterre J. A. M. Nijland; Annemarie M. J. Braamse; Maud M. vanMuilekom; Elisabeth M. J. Suijk; Gerianne M. Hoogendoorn; Charlotte F. J. vanTuijn; Michael R. DeBaun; Bart J. Biemond; Lotte Haverman; Erfan Nur (HemaSphere)
Abstract Advances in conditioning regimens have made non‐myeloablative allogeneic hematopoietic stem cell transplantation (HSCT) a viable curative option for adults with sickle cell disease (SCD). However, prospective studies comparing pre‐ and post‐transplant patient‐reported health outcomes are scarce. Therefore, in a prospective, mixed‐methods cohort study in adults with SCD undergoing HSCT, we tested the hypothesis that physical, mental, and social health improves after HSCT relative to baseline. We compared 9 Patient‐Reported Outcomes Measurement Information System (PROMIS®) measures at 6, 12, and 18 months post‐transplant to baseline and general population values. Semi‐structured interviews were conducted pre‐ and post‐transplant that were thematically analyzed (MAXQDA). Seventeen patients (7 females, 10 males; median age 26 years) underwent matched sibling (9) or haploidentical donor (8) transplantation. Compared to baseline, pain interference (p = 0.008), physical function (p < 0.001), fatigue (p = 0.001), anxiety (p = 0.016), anger (p = 0.037), and the ability to (p < 0.001) and satisfaction with (p < 0.001) social roles and activities improved at 18 months. Compared to reference values, physical function, sleep disturbance, fatigue, anxiety, and the ability to and satisfaction with social roles and activities T‐scores were significantly worse at baseline but comparable or better after 18 months. Thematic analysis of the interviews revealed high satisfaction with improved physical and social abilities alongside complex mental health challenges, including processing the psychological aftermath of SCD, dealing with transplant‐related toxicity, adjustment challenges, and identity conflicts. In conclusion, while physical, mental, and social health improves after HSCT, the effects on mental health can be complex and warrant psychosocial support early in the process of curative therapies.